Representasi Profesi Pustakawan dan Fungsi Perpustakaan (Analisis Semiotika Roland Barthez Terhadap Novel Beta Testing) - Ina Kencana Putri (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2021)
Novel with the tittle Beta Testing is a novel written by an authorl with a pen name Mooseboo and published in 2019. The aim of this research is to look how a novel represented a Libarian as Profession and the function of library. This research using the representation theory as a main theory and used to find and see how a librarian and function of library portrayed. And then the semiotics theory was used as analysis to find a symbols, the meaning and the messages that representing a profession of librarian and the function of library inside this novel. The method used in this research is collecting words or dialogs and then dissected using Roland Barthess semiotics theory. Conclusion that was find from this research is that profession of librarian was represented as, 1) Librarian as helper, 2)Librarian as a educator, 3) Libaraian as a discussion partner, 4) Librarian as a consultant, 5) Librarian as information fasilitator. While the representation of function of library was found ou as, 1) Libarary as a storage collection and 2) Library as education facilities.